African oral art forms and child development: a case of Dominican Nursery and Happy Day Centre in Gweru - Matiza, Vimbai M. (Academic Research Centre, 2022)
African traditional societies had their own ways of raising children which helped them to groom an acceptable African child. In a bid to achieve such, the use of oral art forms was key as these helped develop a child into a good and acceptable member of society. This chapter is given impetus by the fact that contemporary society has changed its modus operandi on how the African child is developed. People now live-in different towns and cities where their children are exposed to various ways of socialisation different from what used to be done in the past. The chapter analyses African oral art forms that developed a child into an acceptable member of society and how the modern African society has adopted the concept through the pre-school. The argument in the chapter emanates from the fact that different societies value different things through the philosophies enshrined in their oral art forms. It is against this same note that the philosophies that are being transmitted to children in two different pre-schools used through the oral tradition may not be the same hence imparting different beliefs. The chapter focuses on aspects of oral literature such as proverbs, songs and poetry among others. In essence, it seeks to explore their role in the socialisation of children in this modern society at early childhood level. Okpewho (1992) defines oral literature as the literature derived by word of mouth whereas Dasylva (2001) conceptualises it as a collective expression and celebration of communal culture specific related experiences which enhance values in traditional societies. By celebration of a communal culture, the authority is bringing to light the idea that these art forms are a creation by community to enhance their teaching to children using concepts they are familiar to. In that regard, the paradox of the matter lies on whose values are being imparted given that children come from different homes. Adejuno (2009) argues that, oral literature is a creative text delivered by word of mouth. It refers to the heritage of the imaginative verbal creations, stories, folk beliefs, songs, riddles, proverbs, songs and spoken word from one generation to another. On the other hand, child development refers to change or growth that occurs in children. It starts with infancy and continues to adulthood. By studying child development, one will form a profile of what children can do and are supposed to do at various ages. That’s why the use of oral art forms was used to facilitate understanding of certain phenomena in the context of culture or the societies that children grow up in. For instance, a two-year-old child when crying would have lullabies being recited to make them cool down and develop the skill of hearing or following the rhythm of the song. This means after hearing those lullabies, children are expected to conform to certain behaviours expressed in the songs, ‘. . . nyarara mwana,. . . mai vake vaendepiko, vaenda mhiri kwaMungezi... ’ (... stop crying baby, ... where has her mother gone, she has gone far away to Mungezi). Likewise, even in this present day, children are being raised through the same process, but the application of these oral art forms is shaped by the environments in which the children grow up in.